Improvement of Resistance Spot Welding by Surfaces Treatment of AA1050 Sheets (Journal of Engineering, 2013)
Resistance spot welding (RSW) aluminum alloys has a major problem of inconsistent quality from weld to weld, because of the problems of the non-uniform oxide layer. The high resistivity of the oxide causes strong heat released which influence significantly on the electrode lifetime and the weld quality. Much effort has been devoted experimentally to the study of the sheet surface characteristics for as-received sheet and surface pretreatment sheet by pickling in NaOH and glassblasted with three thicknesses (0.6, 1.0, and 1.5 mm) of AA1050. Three different welding process parameters energy setup as a low, medium, and high were carried. Tensile-shear strength tests were performed to indicate the weld quality. Moreover, microhardness tests, macro/micrographs, andSEM/EDS examinations were carried out to analyze, compare, and evaluate the effect of surface conditions on the weldability. The as received sheet showed a higher electrical contact resistance because of its thicker and non-uniform oxide layer. In contrast, the glass-blasted sheet showed lower value, since it has a roughest surface, which leads to easy breakdown the oxide layer. The highest average values and least scattering of the maximum load fracture are with treated sheet bypickling in NaOH, these values are 760, 1193, and 2283 N for 0.6, 1.0, and 1.5 mm sheet thickness respectively for medium input energy. In contrast, the minimum values with glass-blasted sheet are 616, 1008, and 2020 N for 0.6, 1.0, and 1.5 mm sheet. The microhardness profiles of the fusion zone and HAZ is the lower than the base metal for all cases. Numerical simulation with SORPAS® was used to simulate and optimize the process parameters, and it has given good results in prediction when they compared with experiments.